Analysis and Conversion of Air Suspension System to Parabolic Leaf Spring Suspension System - Balaji, P; Muralidharan, M; Arun, A; Prakash, E; Chandan Singh, R; Boobalan, K (International Journal of Engineering and Technology, 2018)
Nowadays competition among automobile industries has been increasing rapidly. Hence to retain the existing customers and to make new customers cost and quality of products plays is a rubric one.To do so value engineering plays a vital role. Our project deals with the conversion of air suspension system with parabolic spring suspension system and to prove that it is efficient and economic one compared to air suspension system. It should also be noted that basic functions should be preserved and not to be reduced as a consequence of pursuing value improvements. The aim of the project is to design a parabolic leaf spring for an air suspension system. Parabolic leaf spring is modelled in CATIA software and deformation analysis is done using Ansys 14.Â